Antimicrobial resistance of Staphylococcus aureus strains isolated from cow raw milk samples from Albania and Serbia - Lika, Erinda (Array, 2021)
This research aimed to determine the prevalence rate of antimicrobial resistance (AMR) of Staphylococcus aureus isolated from raw cow milk samples in Albania and Serbia. A total of 100 raw milk samples, 50 from Albania and 50 from Serbia, have been collected from randomly selected cattle farms. Twelve samples (12 %) were positive for S. aureus, five of those originating from Albania (41.66 %) and seven from Serbia (58.33 %). Resistance of isolated S. aureus strains to ampicillin in milk samples from Albania (36.7 %) and Serbia (34.1 %) was the most common. Some of S. aureus strains from milk samples from Albania were resistant to tetracycline (16.9 %), while isolates from milk samples from Serbia were more resistant towards oxacillin (18 %). The recorded resistance towards erythromycin (13.2 %; 13.1 %), and sulfatrim (7.6 %; 6.9 %) was similar between both milk samples, respectively. The obtained results have shown higher resistance of S. aureus strains towards cephalothin in milk samples from Serbia (3.9 %) compared to milk samples from Albania (1.6 %), respectively. All isolates tested for antibiotic sensitivity were susceptible to methicillin, vancomycin, chloramphenicol, and ciprofloxacin. The obtained results regarding the minimum inhibitory concentrations (MICs) of antibiotics indicated that isolates were resistant to tetracycline, oxacillin, erythromycin, and ampicillin, respectively. Results of our investigation have shown that the found antibiotics residues are related to the usage of erythromycin (72.6 % and 73.9 %), followed by ampicillin (70.4 % and 71.2 %) while residues of ciprofloxacin in the analysed milk samples was not registered.